Optimasi Penjadwalan Proyek Perkerasan Jalan Lentur Jalan Konektor POLINELA Menggunakan Critical Path Method berbasis Microsoft Project 2021 - Agustina, Resti (Politeknik Negeri FakFak, 2026)
The area and distance between buildings at POLINELA Campus make the presence of adequate connector roads an important necessity to support the mobility of the academic community. This study aims to optimize the scheduling of flexible pavement construction for the POLINELA Connector Road using the Critical Path Method (CPM) based on Microsoft Project 2021. The research method used is descriptive quantitative by processing the Budget Plan (RAB) data into a project schedule consisting of 11 main activities. CPM analysis is used to determine the sequence of work, dependencies between activities, the critical path, and project completion time. The results show that the total project duration is 23 calendar days (May 11–June 6, 2026). CPM analysis identified 10 activities on the critical path with zero float, while embankment work is a non-critical activity with time flexibility. Applying a Start-to-Start (SS) relationship with a 3-day lag between excavation and embankment work allows parallel implementation, reducing the project duration by 4 days (14.8%) compared to the conventional Finish-to-Start (FS) scenario. These results indicate that implementing CPM through Microsoft Project 2021 can increase execution time efficiency, simplify schedule control, and support decision-making in road construction project management.